Ustekinumab is effective in the treatment of linear psoriasis: a case report and literature review - Qi, Jinxu; Zhu, Qing; Feng, Mengdi; Liu, Lijuan; Zhang, Guoqiang (Frontiers in Immunology, 2025)
Linear psoriasis is a rare type of psoriasis that usually presents as scaly papules and plaques unilaterally distributed along the Blaschko line. Currently, the pathogenesis of linear psoriasis is not fully understood, and genetic mosaicism may be one of the explanations. As linear psoriasis is less responsive to treatment than psoriasis vulgaris, there is no consensus on treatment guidelines specifically for this disease, and the efficacy of ustekinumab in treating this category has not been reported. In this article, we present a case of effective treatment of linear psoriasis with ustekinumab and review the relevant literature, hoping to help clinicians better understand and treat this disease.